Sovereignty Referendums in International and Constitutional Law - Şen, İlker Gökhan. author. aut Link
XIII, 298 p.
Keywords: This book focuses on sovereignty referendums, which have been used throughout different historical periods of democratization, decolonization, devolution, secession and state creation. Referendums on questions of sovereignty and self-determination have been a significant element of the international political and legal landscape since the French Revolution, and have been a central element in the resolution of territorial issues from the referendum in Avignon in 1791 until today. More recent examples include Quebec, East Timor, New Caledonia, Puerto Rico and South Sudan. The global aim of this book is to achieve a better empirical and legal understanding of sovereignty referendums and related problems in international and national law and politics. Accordingly, it presents readers a comprehensive study of sovereignty referendums from the perspectives of both international and constitutional law.